A near-chromosome-scale genome assembly of the gemsbok (Oryx gazella): an iconic antelope of the Kalahari desert. Issue 2 (16th January 2019) - Farré, Marta; Li, Qiye; Zhou, Yang; Damas, Joana; Chemnick, Leona G; Kim, Jaebum; Ryder, Oliver A; Ma, Jian; Zhang, Guojie; Larkin, Denis M; Lewin, Harris A
Abstract: Background: The gemsbok ( Oryx gazella ) is one of the largest antelopes in Africa. Gemsbok are heterothermic and thus highly adapted to live in the desert, changing their feeding behavior when faced with extreme drought and heat. A high-quality genome sequence of this species will assist efforts to elucidate these and other important traits of gemsbok and facilitate research on conservation efforts. Findings: Using 180 Gbp of Illumina paired-end and mate-pair reads, a 2.9 Gbp assembly with scaffold N50 of 1.48 Mbp was generated using SOAPdenovo. Scaffolds were extended using Chicago library sequencing, which yielded an additional 114.7 Gbp of DNA sequence. The HiRise assembly using SOAPdenovo + Chicago library sequencing produced a scaffold N50 of 47 Mbp and a final genome size of 2.9 Gbp, representing 90.6% of the estimated genome size and including 93.2% of expected genes according to Benchmarking Universal Single-Copy Orthologs analysis. The Reference-Assisted Chromosome Assembly tool was used to generate a final set of 47 predicted chromosome fragments with N50 of 86.25 Mbp and containing 93.8% of expected genes. A total of 23, 125 protein-coding genes and 1.14 Gbp of repetitive sequences were annotated using de novo and homology-based predictions. Conclusions: Our results provide the first high-quality, chromosome-scale genome sequence assembly for gemsbok, which will be a valuable resource for studying adaptive evolution of this species and other ruminants.